Fibrin(ogen) in cardiovascular disease: an update - Koenig, Wolfgang (Thrombosis and Haemostasis, 2003)
The notion that fibrinogen is strongly, consistently, and independently related to cardiovascular risk has been widely accepted. The evidence is based on numerous prospective epidemiological studies and clinical observations. In meta-analysis, an association between even modest increases (10%) in fibrino-gen and future coronary heart disease (CHD) endpoints has been found with an odds ratio for CHD of 1.8; 95% CI, 1.6 to 2.0, if the top tertile of the fibrinogen distribution was compared to the bottom tertile; but fibrinogen levels were also associated with unstable and stable coronary artery disease, and coronary complications after interventions. Similar results have been obtained for incident stroke, progression of peripheral arterial disease, and finally for total mortality. The reasons however, why fibrinogen is elevated in cardiovascular disease and in atherosclerosis in general, are only incompletely under-stood; but all cells involved in the atherogenetic process are able to produce cytokines which induce an acute phase reaction, and thus increase fibrinogen plasma levels. The potential pathophysiological mechanisms by which elevated fibrinogen levels mediate cardiovascular risk are manyfold: It forms the substrate for thrombin and represents the final step in the coagulation cascade; it is essential for platelet aggregation; it modulates endothelial function;it promotes smooth muscle cell proliferation and migration; it interacts with the binding of plas-min with its receptor, and finally it represents a major acute phase protein. Whether or not fibrinogen is causally involved in atherothrombogenesis still remains to be determined, and even though other unsolved issues await conclusive answers, fibrino-gen has emerged as an important additional marker of cardiovascular risk.Theme paper: Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: Fibrinogen; cardiovascular risk. epidemiology; clinical evidence; determinants; mechanisms; therapeutic interventions